2022
DOI: 10.1302/0301-620x.104b1.bjj-2021-0869.r2
|View full text |Cite
|
Sign up to set email alerts
|

Mid-term results of Eclipse total shoulder arthroplasty

Abstract: Aims The use and variety of stemless humeral components in anatomical total shoulder arthroplasty (TSA) have proliferated since their advent in 2004. Early outcomes are reassuring but independent mid-term results are scarce. This independent study reports a consecutive series of 143 Eclipse stemless shoulder prostheses with a minimum five-year (5 to 10) follow-up. Methods Outcomes of 143 procedures undertaken for all indications in 131 patients were reviewed, with subset analysis of those for osteoarthritis (O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“… 15 Batten et al included 143 stemless TSA and reported a 5-year implant survival rate of 0.96. 1 Loosening was a rare indication for revision, and the cementless metaphyseal fixation does not seem to have a negative effect on the short-term arthroplasty survival.…”
Section: Discussionmentioning
confidence: 99%
“… 15 Batten et al included 143 stemless TSA and reported a 5-year implant survival rate of 0.96. 1 Loosening was a rare indication for revision, and the cementless metaphyseal fixation does not seem to have a negative effect on the short-term arthroplasty survival.…”
Section: Discussionmentioning
confidence: 99%
“… 1 Conventional anatomic TSA aims to reproduce glenohumeral kinematics with a stemmed humeral component and pegged and/or keeled glenoid components that restore anatomy and centre-of-rotation. Stemmed humeral components remain the gold standard, 2 though over the past decades, manufacturers have shortened stems to reduce risks of malpositioning, loosening and periprosthetic fractures. 3 This led to development of stemless humeral components that restore proximal humeral anatomy without reaming the humeral diaphysis.…”
Section: Introductionmentioning
confidence: 99%
“…3,4,[6][7][8] There are few studies and registries that report mid-term to long-term outcomes after stemless TSA, and information on functional outcomes and implant longevity are therefore lacking. 2,4 The purpose of this study was to report mid-term to long-term clinical outcomes in a multicentre series of patients who received stemless TSA. The hypothesis was that stemless TSA would be a safe and effective treatment with satisfactory mid-term to long-term clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stemmed humeral components remain the gold standard in total shoulder arthroplasty (TSA) and reverse shoulder arthroplasty (RSA). 4 Compared to first-generation implants, manufacturers have short stems in subsequent generations, 2 , 13 with the aim to reduce risks of malpositioning, loosening, and periprosthetic fractures. 14 Recent years have seen a rise in the use of uncemented, press-fit short stems, <10 cm long, 9 as their potential benefits include shorter surgery times, better bone stock preservation in cases of revision, and easier access in shoulders with substantial humeral deformity.…”
mentioning
confidence: 99%